Electrital Electrical Conductivity Control System in Pakcoy Plant based on Fuzzy Logic Control - Siti Ma'shumah; Ellys Kumala Pramartaningthyas (Indonesian Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2021)
Along with increasing consumption of vegetables as a fulfillment of nutrition in the community, it provides a breakthrough to create a new method of growing vegetables, namely using a system of growing vegetables using water called the hydroponic system. In the hydroponic system here using the Nutrient Film Technique (NFT), the NFT technique is a hydroponic cultivation method where roots grow in a shallow nutrient layer and are circulated to get nutrients, water, and oxygen continuously. One of the important things that are a measure of the success of a hydroponic system is the provision of nutrients to plants correctly. The nutrient solution concentration that plants need requires several different electrical conductivity. This study controlled the pakcoy plant using fuzzy logic, consisting of 2 inputs, a TDS sensor and an ultrasonic sensor. At the same time, the output given by the control of this system is the length of the pump opening. The pump for output is divided into 3, and the first is the pump for water, the second is the pump for nutrition A and the last is the pump for nutrition B. In this system, hydroponic nutrient control in pakcoy plants has been tried using fuzzy logic control with a success rate of ±70%. This shows that the system's experiment can run well, namely being able to maintain hydroponic nutrients in pakcoy plants.